Venous Thromboembolism in Patients With Prior Stroke. (January 2014) - Piazza, Gregory; Goldhaber, Samuel Z.; Kroll, Aimee; Goldberg, Robert J.; Emery, Catherine; Spencer, Frederick A.
Patients with prior stroke are susceptible to venous thromboembolism (VTE). We studied patients with stroke in the Worcester VTE study of 2488 consecutive patients hospitalized with VTE. In all, 288 (11.6%) had a clinical history of stroke and 2200 (88.4%) did not. Patients with stroke were more likely to die inhospital (9.2% vs 4%) and within 30 days of VTE diagnosis (16.7% vs 6.9%) compared with patients without stroke (all P < .001). Recent immobilization (adjusted odds ratio [OR] 2.15; 95% confidence interval [CI] 1.15-4.09) and inferior vena cava (IVC) filter insertion (adjusted OR 2.1; 95% CI 1.15-3.83) were associated with a doubling of inhospital death. Recent immobilization (adjusted OR 1.84; 95% CI 1.19-2.83) and IVC filter insertion (adjusted OR 1.94; 95% CI 1.2-3.14) were associated with an increased risk of death within 30 days of VTE. In conclusion, patients with VTE and prior stroke were more than twice as likely to die while hospitalized and within 30 days of VTE diagnosis.